On the closed-end funds discounts/premiums whithin the context of the investor sentiment theory - Monte, Ana Paula (2010)
The purpose of this paper is to present our research on factors that may explain the existence and persistence of the discounts/premiums of closed-end. In this research we use as theoretical framework for closed-end funds discounts/premiums explanations the investor sentiment theory hypothesis. We also investigate the correlation between the discounts/premiums of those funds among themselves and each other over time, the mean reversion of the discounts/premiums, as well as the predictability power of the fund shares and of the net asset value returns. It was also our objective to search for the relevance of the investor sentiment theory in order to explain the discounts/premiums, so that we used Brauer’s (1993) methodology and the signal extraction technique of French and Roll (1986). We also carried out (as far as we know, for the first time) a panel data analysis in order to check how much of the discounts/premiums variability is due to the presence of “noise traders”. This research was based on a sample of 41 North-Americans closed-end funds, that invest mainly on stocks and/or bonds traded on the NYSE or on the AMEX, during the period from January 1987 to June 1999 (inclusive). The data was collected from the Wiesenberger database. From the results that we got, we noticed that there seems to exist an indication of the presence of “noise traders” on the closed-end funds market which, in turn, seems to confirm the assumptions of the investor sentiment theory: the discounts/premiums were positively correlated, were mean reverted and had some predictability power in terms of fund share returns but not so much in relation to their net asset value returns. Nevertheless, we observed that the estimated proportion of the variance of standardised weekly discounts changes, explained by the investor sentiment on the total period studied, was only 8.6%.